2011
DOI: 10.1016/j.idairyj.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of l-cysteine, oxygen and relative humidity upon survival throughout storage of probiotic bacteria in whey protein-based microcapsules

Abstract: a b s t r a c tThe survival rates of Lactobacilus acidophilus Ki, Lactobacillus paracasei L26 and Bifidobacterium animalis BB-12 were studied after whey protein microencapsulation via spray-drying, with or without L-cysteineHCl, and storage up to 6 months at 5 C and 22 C, with variation in relative air humidity and oxygen levels. Lb. paracasei L26 was the least susceptible to storage conditions: above 10 6 cfu g À1 were recorded by 180 d at 22 C, irrespective of relative humidity, and the presence/absence of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 37 publications
5
48
0
Order By: Relevance
“…The results for the encapsulation yield were similar to those obtained by Maciel et al (2014), when evaluating the microencapsulation of L. acidophilus La-5 by using spray drying skim milk and sweet whey (average 76.58%); however, higher than those found by Rodrigues et al (2015) Through the results obtained, were calculated the regression coefficients and it was observed that the quadratic term of the variable concentration of maltodextrin (p < 0.023882) and interaction of the variables temperature of the inlet air atomizer and concentration of maltodextrin (p < 0.043781) were statistically significant (p ≤ 0.10). Thus, there was obtained Equation 1, which represents the quadratic model of Encapsulation Yield of L. acidophilus La-5 as a function of the studied variables.…”
Section: Resultssupporting
confidence: 81%
“…The results for the encapsulation yield were similar to those obtained by Maciel et al (2014), when evaluating the microencapsulation of L. acidophilus La-5 by using spray drying skim milk and sweet whey (average 76.58%); however, higher than those found by Rodrigues et al (2015) Through the results obtained, were calculated the regression coefficients and it was observed that the quadratic term of the variable concentration of maltodextrin (p < 0.023882) and interaction of the variables temperature of the inlet air atomizer and concentration of maltodextrin (p < 0.043781) were statistically significant (p ≤ 0.10). Thus, there was obtained Equation 1, which represents the quadratic model of Encapsulation Yield of L. acidophilus La-5 as a function of the studied variables.…”
Section: Resultssupporting
confidence: 81%
“…Semyonov et al (2011) reported a better stability of L. plantarum in 5DE compared to 19DE MD despite differences in a w (higher a w values of the former). Similarly, SunnyRoberts andKnorr (2009, 2011) showed that the substitution of trehalose by monosodium glutamate (MSG) seemed to increase remarkably the survival rates of L. rhamnosus GG when compared directly to trehalose (despite the alterations of T g values) whereas Rodrigues et al (2011) reported that the detrimental effects of relative humidity and oxygen presence are mainly strain dependent and the presence of HCl cysteine as oxygen scavenger could improve the viability of L. acidophilus.…”
Section: Survival Rates Of the Bacteria During Storagementioning
confidence: 99%
“…paracasei was the least susceptible to storage conditions (temperature, humidity, and time) followed by B. animalis Bb12 while Lb. acidophilus underwent higher losses during storage (Rodrigues et al 2011b). The relative humidity was found to be the most important factor in maintaining the viability during storage of Lb.…”
Section: Post-preparation Behavior Of Probiotic Loaded Wp Micro-beadsmentioning
confidence: 99%